Challenge-driven economic policy: A new frame-work for Germany - Rainer Kattel; Mariana Mazzucato; Keno Haverkamp; Josh Ryan-Collins (Forum for a New Economy, 2020)
German government is stepping into a new era with its COVID-19 recovery support measures. It is leaving behind its ordoliberal foundations which see the role of the state as making sure policy conditions enable markets to function properly. In this view, the state should fix market failures and leave the rest to industry. Already before the pandemic, German policy makers were showing increasing appetite to go beyond market-fixing and experiment with a more overt activist state. With the handling of COVID-19, Germany has taken another step in this direc-tion– it is now at the forefront of taking bold policy action to reshape its economy in the face of the pandemic. Yet, this paper argues Germany's public funding of R&D supports mostly in-cremental advances and its financial system is largely still funding carbon lock-in and value ex-traction rather than transforming the economy to deal with 21st century challenges. Germany needs to build on its recent economic policy initiatives, and successful institutions such as the KfW, and develop a bold new industrial strategy that encompasses science, technology and in-novation, financial and procurement policies. The new industrial strategy is not about 'more state' or 'less state', but a different type of state. One that is able to act as an investor of first resort, catalysing new types of growth, and in so doing crowd in private sector investment and innovation which represent expectations about future growth areas. This requires a new form of collaboration between state and business – more about picking the willing than picking win-ners.
Keywords: E50; G20; H57; L50; O30; 330; Germany; industrial policy; mission-oriented innovation